Pembuatan Flakes Dari Pangan Tepung Beras Merah (Oriza Niavara) Dengan Penambahan Labu Kuning (Cucurbita Moschata Durch - Rizka Octavia; Alfiah Indriastuti; Satriani Napang (Universitas Muslim Indonesia, 2023)
Flakes is a high starch-based product that can increase brown rice consumption. The main raw material that is often used in flakes that are widely circulated in the market is wheat or corn kernels. The raw material is usually processed as a whole or floured first. The flakes that I want to make are flakes products that are good nutritionally and have a sweet and savory taste so they can be consumed directly or with the addition of milk. This study aims to determine the percentage of water content, fiber content, fat content and carbohydrate content with reference to SNI Quality Requirements for Extrudate Snacks according to SNI 01-2886-2000. Then proximate testing was carried out which included testing for water content, fiber content, fat content and carbohydrate content and organoleptic testing which included testing color and taste.